Real time progress management: Re-engineering processes for cloud-based BIM in construction - Matthews, Jane; Love, Peter; Heinemann, S.; Chandler, R.; Rumsey, C.; Olatunj, O. (Elsevier, 2015)
© 2015 Elsevier B.V. All rights reserved. Having timely access to information on the performance of a construction project enables the design team and contractor to improve their decision-making so as to ensure project deliverables are met. This paper examines the effectiveness of cloud-based BIM for real-time delivery of information to support progress monitoring and management of the construction of a reinforced concrete (RC) structure using action based research. To undertake this task, existing paper-based processes were re-engineered to accommodate the use of cloud-based BIM during construction. The design and implementation of a real-time object oriented bi-directional system, allowed information (e.g., the status of the 'As-Built' schedule) to be captured on-site and synchronized with a federated BIM. As a result of adopting cloud-based technology during construction, a new object oriented workflow and processes for progress management are proposed.